2019
DOI: 10.1038/s41586-019-1263-7
|View full text |Cite
|
Sign up to set email alerts
|

Distinct fibroblast subsets drive inflammation and damage in arthritis

Abstract: Summary The identification of lymphocyte subsets with non-overlapping effector functions has been pivotal to the development of targeted therapies in immune mediated inflammatory diseases (IMIDs)1,2. However it remains unclear whether fibroblast subclasses with non-overlapping functions also exist and are responsible for the wide variety of tissue driven processes observed in IMIDs such as inflammation and damage3–5. Here we identify and describe the biology of distinct subsets of fibroblasts responsible for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

50
662
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 661 publications
(760 citation statements)
references
References 28 publications
(44 reference statements)
50
662
3
Order By: Relevance
“…A major remaining question is whether the antibody responses described here contribute to the actual joint inflammation, which is characterized by massive proliferation of synovial fibroblasts and macrophages that invade and destroy cartilage and bone in the joints. Notably, recent studies have pointed out the differential behaviour of different sets of synovial fibroblasts in this process [191,192] however, without providing leads to which factors in the pre-existing immune reactions that may contribute to the development of these phenotypes of synovial fibroblasts. A recently published report from our own group provided evidence that certain ACPAs may indeed activate synovial fibroblasts into a migratory behaviour after binding to citrullinated targets on their cell surface [193]; notably, only synoviocytes that had previously been activated by various stimuli, including pro-inflammatory cytokines and chemokines, were targeted by the ACPAs, thereby providing additional but still circumstantial support for a two-step model of the development of joint inflammation in ACPA-and RF-positive individuals [193].…”
Section: Gene-environment Interactionsmentioning
confidence: 99%
“…A major remaining question is whether the antibody responses described here contribute to the actual joint inflammation, which is characterized by massive proliferation of synovial fibroblasts and macrophages that invade and destroy cartilage and bone in the joints. Notably, recent studies have pointed out the differential behaviour of different sets of synovial fibroblasts in this process [191,192] however, without providing leads to which factors in the pre-existing immune reactions that may contribute to the development of these phenotypes of synovial fibroblasts. A recently published report from our own group provided evidence that certain ACPAs may indeed activate synovial fibroblasts into a migratory behaviour after binding to citrullinated targets on their cell surface [193]; notably, only synoviocytes that had previously been activated by various stimuli, including pro-inflammatory cytokines and chemokines, were targeted by the ACPAs, thereby providing additional but still circumstantial support for a two-step model of the development of joint inflammation in ACPA-and RF-positive individuals [193].…”
Section: Gene-environment Interactionsmentioning
confidence: 99%
“…While fibroblasts have been implicated in inflammation-associated pathology of rheumatoid arthritis, colitis and IPF (7,(15)(16)(17)(18), it has not been shown conclusively whether the stroma is a modifier or primary driver of the inflammatory response. In the BLM model of lung fibrosis, we found that the deletion of IL11 signaling in fibroblasts alone is sufficient to protect mice from inflammation in the lung.…”
Section: Combined Results and Discussionmentioning
confidence: 99%
“…Further studies are required to delineate whether distinct subpopulations of IL11-responsive fibroblasts drive lung fibrosis and inflammation. It will also be important to examine whether IL11-dependent, fibroblast-mediated inflammation occurs in other lung diseases, such as asthma (26,27) or additional conditions such as rheumatoid arthritis or colitis (15)(16)(17)(18). Preliminary functional studies suggest this may be the case, at least for colitis (10), which is characterized by IL11expressing inflammatory fibroblasts that predict disease severity in patients (17).…”
Section: Combined Results and Discussionmentioning
confidence: 99%
“…In rheumatoid arthritis (RA), analysis of synovial tissue with single‐cell RNA sequencing and cytometry by time‐of‐flight mass spectrometry have revealed discrete cell subpopulations with transcriptomic and cell surface expression profiles linked to functional activities . These analyses, focused on the synovium and not the peripheral blood, provided new insights regarding key pathogenic cell–cell interactions and underscore the necessity of examining cellular and molecular events in the target tissue.…”
Section: Characteristics Of Tissue‐resident Memory T Cellsmentioning
confidence: 99%